PENGARUH PENGGUNAAN MEDIA SOSIAL TERHADAP TRANSPARANSI PENGUNGKAPAN INFORMASI PELAPORAN KEUANGAN - Fransiska Widya Pramestika Ariyanti Putri; agnes utari widyaningdyah (Jurnal Akun Nabelo: Jurnal Akuntansi Netral, Akuntabel, Objektif, 2023)
The objective of this study was to empirically examine the effect of social media use on the disclosure transparency of financial reporting information. The design of this research was quantitative research with the data source used was in the form of annual reports listed on the Indonesia Stock Exchange (BEI) year of 2016- 2018. The object of this research was manufacturing and nonfinancial companies. The sample was selected by using purposive sampling method and proportionate stratified random sampling. The data analysis technique used was multiple regression analysis. The results of this study found that the use of social media has a positive effect on the disclosure transparency of financial reporting information. This proves that the use of social media is able to provide transparent disclosure of financial reporting information. Transparent disclosure provides a clear representation of how a company describes its organization. Ultimately, investors can have the information they need to estimate risk in making investment decisions and have longterm trust in the company